Effect of splenic transfer factor on the development of intestinal mucosal barrier in laying hens. (8th October 2022) - Ma, Junxing; Ma, Baochen; Wang, Zixu; Chen, Yaoxing; Ma, Ruiqin; Dong, Yulan
Abstract: BACKGROUND: The aim of this study was to investigate the effects of different doses of chicken spleen transfer factor (TF) on the structure of intestinal epithelial cells in different age groups. One‐day‐old White Leghorns laying hens were randomly divided into four groups: three groups were administered TF at different dosages (0.10, 0.25 or 1.00 mL) and a fourth group was set as control (administered saline, 1.00 mL). Using hematoxylin and eosin staining, high‐throughput sequencing, microbiota analysis, quantitative polymerase reaction and western blotting. RESULTS: We measured the effects of different doses of TF on the following: intestinal mucosal epithelial tissue morphology, intestinal mucosal epithelial barrier‐related gene expression profiles, and intestinal epithelial tight junction gene protein levels. The collected data show that TF can improve the absorption of nutrients by increasing villus height and crypt depth, and regulate intestinal flora disorders. Furthermore, we verified that the expression of the claudin and occludin tight junctions between intestinal epithelial cells was increased with TF. this research is very important for focusing on the structure and gene expression of intestinal tissues. CONCLUSION: The results provide a scientific rationale for feeding and nutrition programs for green and healthy farming, as well as technical support to improve the production efficiency of the livestock and poultry breeding industry. © 2022 Society of Chemical Industry.